Applicability of optical emission spectroscopy techniques for characterization of Ar and Ar/O2 discharges. (27th April 2021) - Nikolić, M; Sepulveda, I; Gonzalez, C; Khogeer, N; Fernandez-Monteith, M
Abstract: Here we explore the accuracy and applicability of two readily—available, low cost techniques: (a) a branching fraction method and (b) an extended corona method (ECM). A three dimensional Monte Carlo simulation was developed to obtain the electron energy distribution function, a necessary parameter in the extended corona model, and we discuss its dependence on oxygen percentage and discharge pressure. The experiment was conducted with a 13.56 MHz radio-frequency capacitive discharge in Ar and Ar with 10% and 20% O2 . Absolute densities of argon resonant 1 s4 and metastable 1 s5 energy levels were calculated at various pressures, powers, and positions inside the resulting plasma using both methods. The ECM was also used for calculation of electron temperature and electron density under the same plasma parameters. Results showed that in pure argon, both methods present a good, inexpensive choice for plasma characterization.